2002
DOI: 10.1093/bioinformatics/18.suppl_1.s22
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence and structure: direct and indirect recognition in protein-DNA binding

Abstract: The starting structure motif was a crystal structure of DNA bound to the integration host factor protein (IHF) of E. coli. IHF is known to exhibit both direct and indirect recognition of its binding sites. (1) Threading DNA sequences onto the crystal structure showed statistically significant partial separation of 60 IHF binding sites from random and intragenic sequences and was positively correlated with binding affinity. (2) The crystal structure was shown to be equivalent to a linear Markov network, and so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 17 publications
0
53
0
1
Order By: Relevance
“…In this study, we have shown that IHF recognizes pre-formed conformational characteristics of the consensus DNA sequence. At all other sites, relative affinity is defined by the conformational freedom of individual base pair steps to adopt the DNA structure of the bound IHF-DNA complex (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we have shown that IHF recognizes pre-formed conformational characteristics of the consensus DNA sequence. At all other sites, relative affinity is defined by the conformational freedom of individual base pair steps to adopt the DNA structure of the bound IHF-DNA complex (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The 8-bp flanking sequences are from the HЈ IHF-binding site; these were held constant. Only the central 34 bp were considered in calculation of deformation energy, as described by Steffan et al (21,22).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations